COMPARATIVE ANALYSIS OF THE MAIN CHARACTER IN THE FILMS "A MAN CALLED OVE BY HANNES HOLM" AND "A MAN CALLED OTTO BY MARC FORSTER" - Nahdhiyah, Nahdhiyah; N, Gusnawati.; Zahra, Annisa Latifa; Pallawa, A Omar; Safril, Dian Ilmarani (Journal of Islamic Culture and Literature (JICeL), 2025)
This study aims to conduct a comparative study of the main characters in two films which are different versions of the same work, namely A Man Called Ove (2015) directed by Hannes Holm and A Man Called Otto (2023) directed by Marc Forster. Both films are positioned as interconnected texts, with an intertextual approach used to analyze narrative changes between the original and remake versions. This intertextual method allows researchers to explore how the spoken texts in the two films interact with each other and shape each other’s meanings. The results of this study reveal significant changes from the original to the remake. This study also found changes in several important aspects: first, the depiction of the main character’s job which is substantially different; second, there are variations in the atmosphere and conversation between the main character and his wife when they first meet; third, the way the main character tells his life story to his neighbors which is different in both versions; and fourth, changes in the development of the narrative told by the main character through the will he wrote. This study provides insight into how remake film adaptations function not only as copies, but also as new constructions that introduce changes in character and narrative depictions. This study contributes to understanding the dynamic relationship between the original text and its adaptation, and how these changes can affect audiences’ interpretations of the characters and story. Keywords: Comparative studies, Intertextual, Original and remake, Narrative changes, film.